A Holistic Assessment of Polyethylene Fiber Ingestion in Larval and Juvenile Japanese Medaka Fish - DiBona, Elizabeth; Pinnell, Lee J.; Heising-Huang, Annika; Geist, Simon; Turner, Jeffrey W.; Seemann, Frauke (Frontiers in Physiology, 2021)
Microplastic pollution is of public concern for global environmental health, aquaculture, and fisheries. Toxicity studies have shown that microplastic ingestion may cause intestinal damage, microbiota dysbiosis, and disturb lipid and energy metabolism in fish. To determine the impact of environmentally relevant, chronic, low dose microplastic fibers on fish health, medaka larvae and juveniles were exposed to five concentrations of polyethylene (PE) fibers for 21 days through the feed. Fish growth & condition were assessed to determine the overall impact on fish health. To identify impaired energy intake, gastrointestinal tract (GIT) integrity was evaluated at the molecular and cellular levels. Microbiota analysis was performed by comparing the top 7 most abundant phyla present in both larval and juvenile fish exposed to 0, 1.5, and 3 PE fibers/fish/day. A shift in the phyla Proteobacteria and Bacteroidetes were observed. Larval samples demonstrated decreased proteobacteria abundance, while juvenile samples displayed an increase in abundance. Relative gene expression of key digestive genes from GIT tissue was quantified using real-time quantitative polymerase chain reaction. An effect on digestive gene expression potentially affecting nutrient absorption and antioxidant production was indicated via a significant decrease of solute carrier family 6 member 6 expression in larvae exposed to 6 fibers/fish/day. No significant molecular changes were observed in juvenile GIT tissue, although a non-monotonous dose-response was observed. GIT morphology was analyzed using histomorphological observations of the GIT mucus and cell types. No significant impairment of the GIT epithelial layers was observed in larvae or juveniles. To assess growth & condition, Fulton's condition factor was measured. No differences were observed in larval or juvenile growth. Comparisons of different developmental stages allowed for identifying vulnerable developmental stages for microplastic exposure; larvae were more susceptible to molecular changes, while shifts in juvenile microbial communities were similar to changes reported post-polystyrene microplastic sphere exposure. This study is one of the first to provide toxicological data on the risk of PE fiber ingestion during fish development stages. Results indicate no imminent threat to fish condition at current measured environmental levels of microplastics; however, close monitoring of vital spawning grounds for commercially important fishes is recommended.